Dediščina soške fronte kot izhodišče za razmislek o sodobnih pristopih k dediščinski politiki - Kravanja, Boštjan (Etnolog. Nova vrsta (Ljubljana), 2018)
Current events marking 100 years since end of the First World War have given a huge boost to the heritage of the Isonzo Front. The Kobarid Museum and the "Walk of Peace in the Soča Region Foundation" are results of local enthusiasm, but also cross-border regional EU politics and national efforts for recognition of Republic of Slovenia within European politics. The article treats the question of heritage management and demonstrates how the heritage stakeholders in Kobarid have since always coordinated its use with European and national heritage politics and with heritage trends in the world.
Keywords: Battles of the Isonzo; cultural heritage; dediščinska politika; kulturna dediščina; prva svetovna vojna; Slovenia; Slovenija; soška fronta; temačna dediščina; tourism; turizem; Unesco; upravljanje dediščine; World War I